ON THE ROLE OF THE "CULTURAL REVOLUTION" IN THE SOCIO- ECONOMIC LIFE OF CHINA: EYEWITNESS ACCOUNTS AND MODERN ASSESSMENTS - Khajiyeva, G. (Journal of Oriental Studies, 2023)
The article examines the phenomenon of the "Cultural Revolution", one of the most controversial and tragic phenomena in the history of China. The author attempts a comprehensive assessment of the "Cultural Revolution", its impact on the course of the historical process in China. The inner logic and deep understanding of the prerequisites, goals, essence and role of this phenomenon are revealed through the prism of scientific and memoir works written by eyewitnesses of the events that took place in the 1966s and 1976s in China. The article was prepared on the basis of research conducted within the framework of the scientific project "Oral history of migration from China to Kazakhstan in the 1950s-1970s". This work was carried out in order to identify the consequences of such a radical and large-scale campaign for the political and socio-economic spheres of Chinese society, the degree of its influence on the forced migration of the 1950s and 1970s from China to Kazakhstan. The reconstruction of the course of events of the "Cultural Revolution" was carried out using the method of historical detail, which allows us to study this difficult period in stages, and at each stage revealed exactly those features, events, reforms that entailed negative political and social consequences that affected the migration intentions of the population. An assessment of the events of the period of the "Cultural Revolution", which completed a series of political campaigns and economic experiments of the first decades of the People's Republic of China, helps to understand its impact on the domestic and foreign policy of the country, as well as the peculiarities of the political and socio-economic development of modern China. Because just two years after the end of the "Cultural Revolution", deep economic reforms and market transformations began in the country, which contributed to the transformation of China into a world economic power. Key words: China, political campaign, cultural revolution, ideology, economic consequences, social upheavals.